2020
DOI: 10.21037/tcr.2020.04.17
|View full text |Cite
|
Sign up to set email alerts
|

The value of intra-procedural transcatheter intraarterial contrast-enhanced ultrasonography (IA-CEUS) in predicting the short-term efficacy of conventional transarterial chemoembolization (cTACE)

Abstract: Background This study aimed to evaluate whether corona enhancement and intratumor perfusion features of intra-procedural transcatheter intraarterial contrast-enhanced ultrasonography (IA-CEUS) predict short-term tumor response on follow-up contrast-enhanced magnetic resonance imaging (CE-MRI) in patients with hepatocellular carcinoma (HCC) treated with conventional transarterial chemoembolization (cTACE). Methods This trial included 39 patients with 51 HCC target lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…28 When evaluating the tumor response of the TACE in HCC, CEUS can dynamically observe the real-time change in the microcirculation of the entire tumor after TACE, the intratumoral perfusion, and also changes in the local drainage area around the tumor. 29 There are several limitations of our study that should be addressed in a future study. First, CDI, PDI, and SMI were performed in a sequential manner in each patient, thus, there is potential for recall bias.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…28 When evaluating the tumor response of the TACE in HCC, CEUS can dynamically observe the real-time change in the microcirculation of the entire tumor after TACE, the intratumoral perfusion, and also changes in the local drainage area around the tumor. 29 There are several limitations of our study that should be addressed in a future study. First, CDI, PDI, and SMI were performed in a sequential manner in each patient, thus, there is potential for recall bias.…”
Section: Discussionmentioning
confidence: 94%
“…CEUS could be performed immediately after TACE 28 . When evaluating the tumor response of the TACE in HCC, CEUS can dynamically observe the real‐time change in the microcirculation of the entire tumor after TACE, the intratumoral perfusion, and also changes in the local drainage area around the tumor 29 …”
Section: Discussionmentioning
confidence: 99%
“…Even if this phenomenon is demonstrated by CBCT in this case, the consistency of CBCT and CEUS in the display of drainage areas needs further study. In our previous study, we found that the consistency between the drainage area and short-term TR, as evaluated by MRI, was good [ 28 ]. In addition, a decrease in drainage area can be explained by a decrease in blood supply within the tumour.…”
Section: Discussionmentioning
confidence: 99%